THE PEOPLE’S DEMOCRATIC PARTY OF UZBEKISTAN TODAY: VOICE OF SOCIAL JUSTICE IN A TRANSFORMING POLITICAL LANDSCAPE - Shohruhmirzo Qosimov (Bright Mind Publishing, 2025)
The People’s Democratic Party of Uzbekistan (PDPU) occupies a significant position within the country’s evolving political system. As a party committed to social justice, equality, and the protection of vulnerable groups, the PDPU has consistently advocated for policies that promote welfare, support for pensioners, people with disabilities, and low-income families. In the context of Uzbekistan’s ongoing political and socio-economic transformation, the PDPU has adapted its strategies to remain relevant and influential. The party’s focus on engaging youth, enhancing civil society participation, and contributing to legislative processes underscores its role as a key actor in fostering inclusive governance. This article aims to provide a comprehensive overview of the PDPU’s current ideological orientation, organisational structure, policy priorities, and its impact on Uzbekistan’s political landscape. By examining these dimensions, the study highlights the party’s contributions to social equity and political pluralism in a rapidly changing environment.